Optimal synthesis of energy efficient distillation columns sequence of natural gas liquids - Mohd Faris, Mustafa; Noor Asma Fazli, Abdul Samad; Norazana, Ibrahim; Kamarul Asri, Ibrahim; Mohd Kamaruddin, Abd Hamid (RCChE, 2014)
The objective of this paper is to present the study and analysis of the energy saving improvement for the NGLs fractionation plant sequence by using driving force method. To perform the study and analysis, the energy efficient NGLs fractionation plant sequence methodology is developed. Accordingly, the methodology consists of four hierarchical steps; Step 1: Existing Sequence Energy Analysis, Step 2: Optimal Sequence Determination, Step 3: Optimal Sequence Energy Analysis, and Step 4: Energy Comparison. The capability of this methodology is tested in designing minimum energy distillation column sequence for NGLs fractionation process. The results show that the maximum of 46% energy reduction was able to achieve by changing the sequence suggested by the driving force method. It can be concluded that, the sequence determined by the driving force method is able to reduce energy used for NGLs fractionation process. All of this findings show that the methodology is able to design minimum energy distillation column sequence for NGLs fractionation process in an easy, practical and systematic manner.